Chemotype differentiation and environmental drivers of bioactive metabolites in Cordyceps chanhua from diverse geographical origins - Qiucheng Luo; Gangxiang Fei; Xiaoguang Tian; Shuang Han; Jingqiang Guan; Bo Song; Longzhan Gan; Yeming Zhou; Zhijie Wang; Hongbo Lan; Xiao Zou (Biochemical Systematics and Ecology, 2026)

Structural diversity offsets the mortality risk of tree species richness while enhancing productivity in subtropical plantations - Yuli Liao; Jian Wang; Hui Wang; Shirong Liu; Yeming You; Xueman Huang; Ji Zeng; Xiuli Tong; Jihuang Xu (Forest Ecology and Management, 2026)

A Nile Red-assisted colorimetric and SERS dual-mode strategy for the rapid and highly sensitive detection of nanoplastics - Zhaoyan Yang; Gujie Pei; Jinlin Zhang; Bing Chen; Yeming Qing; Kuo Yang; Dan Zhu; Bingxiang Li; Zhuyuan Wang (Analytica Chimica Acta, 2026)

Enhancing soil aggregate stability in mixed plantation of Eucalyptus urophylla and Acacia mangium - Yeming You; Danyang Hou; Hailun Ma; Yi Wang; Yijia Huang; Zhouyu Luo; Haimei Huang; Lu Zheng; Xueman Huang (Applied Soil Ecology, 2026)

Respiratory viral sepsis: rethinking fluid resuscitation and antibiotic stewardship - Dong Liu; Mengwei Yan; Di He; Zai Wang; Yeming Wang; Bin Cao (Science China Life Sciences, 2026)

An exploration on coconut milk stability by protein characterization, sterilization controlling, and alternative protein emulsifiers - Yuqing Wang; Ruoyu Xing; Suyu Jin; Caimeng Zhang; Yufei Hua; Yeming Chen; Xiangzhen Kong (Food Chemistry, 2026)

Physicochemical properties and flavor profile of coconut yoghurt: the dual role of fat reduction and protein fortification - Jiawei Dai; Ruoyu Xing; Yuqing Wang; Caimeng Zhang; Yufei Hua; Yeming Chen; Xingfei Li; Xiangzhen Kong (Food Research International, 2026)

Investigation of the hydrodynamic characteristics of the underwater propulsion pump blade based on a bionic strategy - Miao Jin; Haoran Liu; Guoyong Jin; Fangming Zhou; Yeming Lu; Xiaofang Wang (Ocean Engineering, 2025)

Volatile flavor characterization of raw coconut milk and the impact of sterilization: A comparative analysis for coconut flavor preservation - Ruoyu Xing; Yuqing Wang; Jiawei Dai; Caimeng Zhang; Yufei Hua; Yeming Chen; Xiangzhen Kong (Food Chemistry, 2025)

Proteolysis and lipolysis induced by acidification of sesame seeds - Xinyu Wang; Lili Wang; Lijuan Wang; Caimeng Zhang; Xiangzhen Kong; Yufei Hua; Yeming Chen (Food Chemistry, 2025)

A wash-free red fluorescent probe for real-time monitoring of mitochondrial viscosity changes and tumor imaging - Kun Yu; Yeming Zhang; Yuqing Wang; Jiale Li; Jie Wang; Sichen Zhang; Aobo Sun; Xue Zhang; Lei Hu; Hui Wang (Journal of Photochemistry and Photobiology B: Biology, 2025)

Longitudinal landscape of immune reconstitution after acute SARS-CoV-2 infection at single-cell resolution - Lili Ren; Yiwei Liu; Yeming Wang; Chao Wu; Li Guo; Lan Chen; Xinming Wang; Yan Xiao; Lixue Huang; Jingchuan Zhong; Jiacheng Yao; Lu Liu; et al. (Science Bulletin, 2025)

Impact of solvent and water activity on lipase selectivity and acyl migration of ARA-rich 2-monoacylglycerols in catalytic systems: Kinetic study by particle swarm optimization - Youfeng Zhang; Xiaohan Wang; Yijie Fu; Xintong Wang; Junwen Yu; Yeming Chen; Xiaosan Wang (Food Chemistry, 2025)

Flow-heat coupling analysis of the 1/4 symmetrical CAP1400 nuclear island loop based on the source term approach - Yeming Lu; Zhenyang Guo; Meina Zhang; Meina Zhang; Xiaomo Jiang; Xiaofang Wang (Annals of Nuclear Energy, 2025)

Introducing N2-fixing tree species into Eucalyptus plantations increases organic phosphorus transformation but decreases its accumulation within aggregates in subtropical China - Haocheng Xu; Yeming You; Yi Wang; Guannv Gao; Angang Ming; Xueman Huang (Plant and Soil, 2024)

Spatial pattern, source apportionment, and source-oriented health risk quantifying of heavy metals in farmland soils of southern China - Bifeng Hu; Xiangyu He; Jiumao Zhou; Hong Zhang; Yeming Dai; Zhige Wang; Yefeng Jiang; Yangzhu Zhang; Pengbo Zhang; Zhou Shi (Environmental Monitoring and Assessment, 2024)

Fine particulate matter concentration prediction based on hybrid convolutional network with aggregated local and global spatiotemporal information: A case study in Beijing and Chongqing - Qiaolin Zeng; Yang Cao; Meng Fan; Liangfu Chen; Hao Zhu; Lihui Wang; Yeming Li; Sizhu Liu (Atmospheric Environment, 2024)

Conversion of pure Chinese fir plantation to multi-layered mixed plantation increases organic phosphorus accumulation and transformation within soil aggregates - Haimei Huang; Xueman Huang; Yi Wang; Jiajun Li; Mingzhu Xiang; Changhang Li; Shushou Liao; Yeming You (Applied Soil Ecology, 2024)

Effectiveness and safety of Sanhan Huashi granules versus nirmatrelvir–ritonavir in adult patients with COVID-19: A randomized, open-label, multicenter trial - Xiaohui Zou; Kang Chang; Guohui Fan; Huanwei Zheng; Hezheng Shen; Liang Tang; Yingying Yang; Yeming Wang; Linhua Zhao; Hong Lv; Xin Zhou; Xiaoming Shen; et al. (Science Bulletin, 2024)

Characterization of mung bean endogenous proteases and globulins and their effects on the production of mung bean protein - Qianqian Zhou; Lili Wang; Yaowen Zhang; Caimeng Zhang; Xiangzhen Kong; Yufei Hua; Yeming Chen (Food Chemistry, 2024)

Estimation of ground-level O3 concentration in the Yangtze River Delta region based on a high-performance spatiotemporal model MixNet - Qiaolin Zeng; Yechen Wang; Jinhua Tao; Meng Fan; Songyan Zhu; Liangfu Chen; Lihui Wang; Yeming Li (Science of The Total Environment, 2023)

Full-coverage estimation of PM2.5 in the Beijing-Tianjin-Hebei region by using a two-stage model - Qiaolin Zeng; Yeming Li; Jinhua Tao; Meng Fan; Liangfu Chen; Lihui Wang; Yechen Wang (Atmospheric Environment, 2023)

Underwater propeller turbine blade redesign based on developed inverse design method for energy performance improvement and cavitation suppression - Yeming Lu; Zhenyang Guo; Zeyu Zheng; Wei Wang; Hui Wang; Fangming Zhou; Xiaofang Wang (Ocean Engineering, 2023)

Cerebral ischemic injury after transcatheter aortic valve replacement in patients with pure aortic regurgitation - Xianbao Liu; Hanyi Dai; Jiaqi Fan; Dao Zhou; Gangjie Zhu; Abuduwufuer Yidilisi; Jun Chen; Yeming Xu; Lihan Wang; Jian’an Wang (Journal of Zhejiang University-SCIENCE B, 2023)

Comparison of physicochemical properties and volatile flavor compounds of plant-based yoghurt and dairy yoghurt - Xinlu Wang; Xiangzhen Kong; Caimeng Zhang; Yufei Hua; Yeming Chen; Xingfei Li (Food Research International, 2023)

Study of the Operating Characteristics for the High-Speed Water Jet Pump Installed on the Underwater Vehicle with Different Cruising Speeds - Yeming Lu; Haoran Liu; Xiaofang Wang; Hui Wang (Journal of Marine Science and Engineering, 2021)
Due to the higher propulsive efficiency, lesser vibration, and better maneuverability, the water jet pump is widely applied to high-speed underwater vehicles. By taking a newly developed water jet pump system as the object, the corresponding underwater vehicle’s operating characteristics affected by different cruising speeds (15.43, 30.86, and 52.47 m/s) were investigated. The steady results reply that the cruising speed increase will result in the decline of the overall performances comprised of the head, the efficiency, the thrust, and the power. While, by using different analyzing methods, the unsteady results are listed as follows: (1) The energy loss theory denotes that the increasing cruising speed promoted the kinetic energy diffusion from the Reynolds stress and viscous stress and depress the turbulent kinetic energy production and the viscous dissipation. (2) The statistical PLS method reveals that the tip load effect on the leakage flow becomes weaker when the cruising speed becomes larger, while the effect from the scraping pressure has a completely opposite trend. (3) Further unsteady analysis implies that the increasing cruising speed makes the pressure pulsation larger and makes the radial force, the axial force, and the cloudy cavity size smaller.

Design, synthesis and anticancer activities of halogenated Phenstatin analogs as microtubule destabilizing agent - Shengquan Hu; Wuji Sun; Yeming Wang; Hong Yan (Medicinal Chemistry Research, 2019)

Microbial community and associated enzymes activity influence soil carbon chemical composition in Eucalyptus urophylla plantation with mixing N2-fixing species in subtropical China - Xueman Huang; Shirong Liu; Yeming You; Yuanguang Wen; Hui Wang; Jingxin Wang (Plant and Soil, 2017)

Spatial concentration, impact factors and prevention-control measures of PM2.5 pollution in China - Xianhua Wu; Yufeng Chen; Ji Guo; Guizhi Wang; Yeming Gong (Natural Hazards, 2017)

Pliocene charcoals from Shanxi Province of China and their application to studies of prehistoric wildfires - YeMing Cheng; XiaoMei Jiang; ChengSen Li; YuFei Wang (Science China Earth Sciences, 2011)

Mechanism for the rapid motion of the Qianjiangping landslide during reactivation by the first impoundment of the Three Gorges Dam reservoir, China - Fawu Wang; Yeming Zhang; Zhitao Huo; Xuanming Peng; Shimei Wang; Shintaro Yamasaki (Landslides, 2008)

Movement of the Shuping landslide in the first four years after the initial impoundment of the Three Gorges Dam Reservoir, China - Fawu Wang; Yeming Zhang; Zhitao Huo; Xuanming Peng; Kiminori Araiba; Gonghui Wang (Landslides, 2008)

Expression of Human Calcitonin by Microencapsulated Recombinant Myoblasts - Yeming Wang; Bingfang Zeng; Xiaolin Li (Biotechnology Letters, 2006)